2008
DOI: 10.1091/mbc.e08-02-0159
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 Targets Sprouty2 and Promotes Cellular Outgrowths

Abstract: The posttranscriptional regulator, microRNA-21 (miR-21), is up-regulated in many forms of cancer, as well as during cardiac hypertrophic growth. To understand its role, we overexpressed it in cardiocytes where it revealed a unique type of cell-to-cell "linker" in the form of long slender outgrowths and branches. We subsequently confirmed that miR-21 directly targets and down-regulates the expression of Sprouty2 (SPRY2), an inhibitor of branching morphogenesis and neurite outgrowths. We found that beta-adrenerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
229
2
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 337 publications
(245 citation statements)
references
References 60 publications
(69 reference statements)
11
229
2
2
Order By: Relevance
“…This concept was first introduced in the context of "miRNA sponges," a term coined for transgenes containing multiple miRNA-binding sites that act as competitive inhibitors of a miRNA (35). In several cases, sponges, or related constructs, have also been shown to cause a reduction in the level of the endogenous miRNA (36,37). Ameres et al (38) recently showed that extensive complementarity between a miRNA and an artificial target can induce miRNA degradation in flies, which was also observed in HeLa cells.…”
Section: Discussionmentioning
confidence: 99%
“…This concept was first introduced in the context of "miRNA sponges," a term coined for transgenes containing multiple miRNA-binding sites that act as competitive inhibitors of a miRNA (35). In several cases, sponges, or related constructs, have also been shown to cause a reduction in the level of the endogenous miRNA (36,37). Ameres et al (38) recently showed that extensive complementarity between a miRNA and an artificial target can induce miRNA degradation in flies, which was also observed in HeLa cells.…”
Section: Discussionmentioning
confidence: 99%
“…Among the targets, we chose Spry2 containing a miR-21 seed match in its 3 0 untranslated region (UTR), as it is known to negatively regulate Ras signaling (Cabrita and Christofori, 2008). Moreover, it has been reported that miR-21 targets Spry2 in cardiocytes and colon cancer SW480 cells (Sayed et al, 2008). We constructed a reporter plasmid (wt-UTR), driven by SV40 basal promoter, harboring the 778-nucleotide wt-3 0 UTR of Spry2 at the 3 0 position of luciferase reporter gene.…”
Section: Mir-21 Targets Spry2 For Glioma Invasionmentioning
confidence: 99%
“…Repression of miR by corresponding miR TS is possible, but only when the miR TS are expressed from a strong promoter at very high levels and/or the transgene contains multiple tandem miR TS (X6), which preferentially contain a bulge at position 9-12 to prevent RNA interference type endonucleolytic cleavage of the miR-miR TS duplex by Argonaute 2. 26,42,43 None of these features are characteristics of the miR-regulated AAV vectors used here. Therefore, AAV vectors with miR122 TS are obviously unable to deregulate endogenous miR122 expression levels and induce side effects.…”
Section: -δδCtmentioning
confidence: 99%